Optimization of processing parameters and accelerated shelf life of kerisik - Mohamad, Naemaa (2014)
The study was conducted since there is no information about optimization of kerisik (roasted coconut paste) processing parameters and accelerated shelf life study of the optimized processing parameters of kerisik to date. Therefore, the objectives of the study were to use response surface methodology (RSM) to optimize roasting temperature and roasting time to produce kerisik and consequently to use accelerated shelf life study to determine the shelf life of the kerisik. The optimization of kerisik processing parameters such as roasting temperature (130-150 °C) and roasting time (210-240 minutes) was achieved by using central composite design (CCD) via Design Expert software. Responses measured were color (L and b values) and furan compound (measured at 280 and 290 nm). Subsequently, the kerisik were packed in nylon and polypropylene packaging films and then were stored at two storage temperatures namely 38 °C for 38 days and 48 °C for 30 days for each type of packaging film. The analyses for accelerated shelf life study included moisture content (%), total color different (TCDH), peroxide value (PV) (meq kg-1), acid value and p-anisidine value. Accelerated shelf life study employed PV as it main parameter in shelf life estimation with PV of 10 meq per kg fat was considered as the threshold limit for oxidative rancidity. Result showed that the optimum processing conditions for kerisik (laboratory scale) by using oven were found to be 130 °C (roasting temperature) for 227 minutes (roasting time). Predicted value of responses (color and furan) obtained using model equations were in good agreement with the experimental values. L (lightness), b (yellowness) and furan measured at 280 and 290 nm were significantly affected by the processing parameters. Finally, the shelf life of kerisik in nylon packaging film was predicted to be 46-49 days and 41-43 days for kerisik in polypropylene film. Kerisik producers may consider the generated optimized processing parameters and accelerated shelf life information from this study for kerisik product development in order to find the best method to replace the conventional way of kerisik production.